PENGARUH SPEED READING TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Agustini, Jumaidha; Halidjah, Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractSpesial aims this study was to analyze the effect of speed reading on comprehension reading skills and to analyze how much influence the use of speed reading on comprehension reading skills in class V West Pontianak 56 Elementary School. Procedure this study uses an experimental method with Experimental Design type One Group Pretest-Posttest Design. The population was all fifth grade students of West Pontianak Public Elementary School 56 amunt to of 80 students, sampling a non-probability sampling technique with of simpel random sampling , namely all VB classes of 56 Pontianak West Elementary Schools, totaling 26 student. The technique used in data collection was technique the measurement with the data collection tool used was an essai form written test. Based on data analysis obtained the results of the average student pre-test was 65 and the average post-test results of students was 74.23. After the t test was obtained the count is 14.359 while the table was 2.059, which means as t test (14.359) > t table (2.059), then hypothesis alternative was accepted. Based on calculation of the effect size (ES) obtained result 0.5523. So, it can be concluded that there was influence of speed reading on comprehension reading skills of west pontianak 56 elementary schools. Keywords: Comprehension Reading Skills, Influence, Speed Reading.